Trapping success and flight behavior of two parasitoid species of the woodwasp Sirex noctilio - Martinez Von Ellrich, Andres; Fischbein, Deborah; Villacide, Jose Maria; Corley, Juan Carlos (Elsevier, 2019)
Classical biological control relies on the deliberate introduction of natural enemies to reduce pest populations below damage thresholds. Knowledge on key aspects of the behavior of antagonists and their population densities through time can be important to increase the efficiency of control programs. The woodwasp Sirex noctilio is a global threat to pine forests and biological control can be based, among other agents on two parasitoids, Ibalia leucospoides and Megarhyssa nortoni, with variable success. Currently no sensitive and standardized monitoring method exists for these control agents and little is known on their behavior, such as their vertical flight-distribution. Our aims were: firstly, assess the efficiency in capturing the parasitoids of four methods (two passive traps based on flight-path interception or caging previously-attacked trees to retain emerging insects, and two active traps baited with pine volatiles), and secondly establish the parasitoids vertical flight distribution. Ibalia leucospoides (females) was captured by all methods but intercept panel traps registered the highest captured individuals when accounting for effort. Conversely M. nortoni did not respond to baited traps, and low numbers were recorded in passive traps. Males of both species flew higher than females of I. leucospoides. Intercept traps baited with pine volatiles could be used to monitor I. leucospoides, but M. nortoni is not captured in these traps. We suggest that both species could be monitored by passively trapping insects at the moment of emergence from previously-infested trees. Further research is needed, especially on the chemical ecology of both species, to further develop inexpensive and standardized monitoring methods.